Knockdown long non-coding RNA ANRIL inhibits proliferation, migration and invasion of HepG2 cells by down-regulation of miR-191 - Huang, Deyu (BMC Cancer, 2018)
BACKGROUND: Hepatocellular carcinoma (HCC) is a common malignant tumor with high fatality rate. Recent studies reported that up-regulation of long non-coding RNA antisense non-coding RNA in the INK4 locus (lncRNA ANRIL) was found in HCC tissues, and which could affect HCC cells biological processes. However, the potential molecular mechanism of ANRIL in HCC is still unclear. The study aimed to uncover the effect of ANRIL on HepG2 cells growth, migration and invasion. METHODS: The knockdown expression vectors of ANRIL were transfected into HepG2 cells, and qRT-PCR, CCK-8, flow cytometry, Transwell and western blot assays were performed to analyze the effect of ANRIL on cell proliferation, apoptosis, migration and invasion. The relative expression of miR-191 was then examined in ANRIL knockdown vector transfected cells. These experiments were repeated again for exploring the effect of miR-191 on HepG2 cells. NF-κB and Wnt/β-catenin signaling pathways were examined by using western blot assay. RESULTS: Knockdown of ANRIL inhibited proliferation, induced apoptosis, meanwhile suppressed migration and invasion of HepG2 cells. Additionally, the results showed that the expression level of miR-191 was down-regulated by ANRIL knockdown in HepG2 cells. Importantly, overexpression of miR-191 reversed the anti-tumor effect of ANRIL on cell proliferation, apoptosis, migration and invasion in HepG2 cells. Besides, we found that ANRIL knockdown inactivated NF-κB and Wnt/β-catenin pathways by regulating miR-191. CONCLUSIONS: These data demonstrated that ANRIL knockdown suppressed proliferation, migration, invasion, and promoted apoptosis in HepG2 cells by down-regulating miR-191 and inactivating NF-κB and Wnt/β-catenin signaling pathways.